Modeling and simulation of bus assem-bling process using DES/ABS approach - Pawlewski, Pawel; Kluska, Kamila (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2017)
This paper presents the results of the project, which goal is to analyze the production process capability after reengineering the assembly process due to expansion of a bus production plant. The verification of the designed work organization for the new configuration of workstations on new production hall is necessary. To solve these problems authors propose a method based on mixing DES (Discrete Event Simulation) and ABS (Agent Based Simulation) approach. DES is using to model the main process – material flow (buses), ABS is using to model assembling operations of teams of workers. One of obtained goal is to build a simulation model, which presents the new assembly line in the factory, taking into ac-count the arrangement of workstations and work teams in the new production hall as well as the transport between workstations. Second goal is to present work organization of work teams and division of individual workers’ labor (who belongs to a particular work team and performs operations on buses in a particular workstation) in order to determine the best allocation of tasks and the optimum size of individual work teams. Proposed solution enables to determine the effect of assembly interferences on the work of particular work teams and the efficiency of the whole production system, to define the efficiency of the designed assembly lines and proposing changes aimed at the quality improvement of the created conception.